2015
DOI: 10.1111/ajt.13182
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function in De Novo Liver Transplant Recipients Receiving Different Prolonged-Release Tacrolimus Regimens—The DIAMOND Study

Abstract: DIAMOND: multicenter, 24‐week, randomized trial investigating the effect of different once‐daily, prolonged‐release tacrolimus dosing regimens on renal function after de novo liver transplantation. Arm 1: prolonged‐release tacrolimus (initial dose 0.2mg/kg/day); Arm 2: prolonged‐release tacrolimus (0.15–0.175mg/kg/day) plus basiliximab; Arm 3: prolonged‐release tacrolimus (0.2mg/kg/day delayed until Day 5) plus basiliximab. All patients received MMF plus a bolus of corticosteroid (no maintenance steroids). Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 5 publications
10
70
3
2
Order By: Relevance
“…The study design was similar to that of the ReSpECT study, with 857 liver transplant recipients receiving MMF and a single bolus of intraoperative corticosteroids, in combination with one of the following: standard-dose, prolonged-release tacrolimus (target trough level, 5-15 ng/mL until day 42 then 5-12 ng/mL); lower-dose, prolongedrelease tacrolimus (4-12 ng/mL until day 42 then reduced by 20-25%) and basiliximab; or standard-dose, prolongedrelease tacrolimus (5-15 ng/mL until day 42) delayed until day 5 and basiliximab. 171 Results from this study indicated that lower-dose, prolonged-release tacrolimus administered immediately posttransplant (and a subsequent lower tacrolimus exposure over the first month), together with MMF and basiliximab, was associated with a significant renal function benefit and a significantly lower incidence of biopsy-confirmed acute rejection (BCAR) versus the standard-dose, prolongedrelease tacrolimus-based regimen (Figure 11). 171 Delayed initiation of standard-dose, prolonged-release tacrolimus significantly reduced renal function impairment; however, the BCAR incidence advantage was not seen with delayed initiation (Figure 11).…”
Section: Underimmunosuppression In Liver Transplantationmentioning
confidence: 90%
See 2 more Smart Citations
“…The study design was similar to that of the ReSpECT study, with 857 liver transplant recipients receiving MMF and a single bolus of intraoperative corticosteroids, in combination with one of the following: standard-dose, prolonged-release tacrolimus (target trough level, 5-15 ng/mL until day 42 then 5-12 ng/mL); lower-dose, prolongedrelease tacrolimus (4-12 ng/mL until day 42 then reduced by 20-25%) and basiliximab; or standard-dose, prolongedrelease tacrolimus (5-15 ng/mL until day 42) delayed until day 5 and basiliximab. 171 Results from this study indicated that lower-dose, prolonged-release tacrolimus administered immediately posttransplant (and a subsequent lower tacrolimus exposure over the first month), together with MMF and basiliximab, was associated with a significant renal function benefit and a significantly lower incidence of biopsy-confirmed acute rejection (BCAR) versus the standard-dose, prolongedrelease tacrolimus-based regimen (Figure 11). 171 Delayed initiation of standard-dose, prolonged-release tacrolimus significantly reduced renal function impairment; however, the BCAR incidence advantage was not seen with delayed initiation (Figure 11).…”
Section: Underimmunosuppression In Liver Transplantationmentioning
confidence: 90%
“…171 Results from this study indicated that lower-dose, prolonged-release tacrolimus administered immediately posttransplant (and a subsequent lower tacrolimus exposure over the first month), together with MMF and basiliximab, was associated with a significant renal function benefit and a significantly lower incidence of biopsy-confirmed acute rejection (BCAR) versus the standard-dose, prolongedrelease tacrolimus-based regimen (Figure 11). 171 Delayed initiation of standard-dose, prolonged-release tacrolimus significantly reduced renal function impairment; however, the BCAR incidence advantage was not seen with delayed initiation (Figure 11). 171 Results from this study indicate that early tacrolimus exposure in the immediate posttransplant period may be critical in maintaining renal function over the long term.…”
Section: Underimmunosuppression In Liver Transplantationmentioning
confidence: 90%
See 1 more Smart Citation
“…Results from a 24-week study of 857 liver transplant recipients (Figure 8) indicated that lower-dose prolonged-release tacrolimus capsules (0.15-0.175 mg/kg per day subsequently reduced by 20-25%, target trough level, 4-12 ng/mL) a , administered with MMF and basiliximab immediately posttransplant, was associated with a significant renal function benefit and a significantly lower incidence of biopsy-confirmed acute rejection, compared with a higher-dose (5-15 ng/mL until day 42 then 5-12 ng/mL) prolonged-release tacrolimus-based regimen. 178 The Impact of Underimmunosuppression…”
Section: Evidence For Cni-minimization Strategiesmentioning
confidence: 99%
“…251 The randomized controlled DIAMOND study (Figure 8) showed that an initial lower dose prolongedrelease tacrolimus capsules regimen, or the delayed initiation (Day 5) of the higher dose prolonged-release tacrolimus capsules regimen (together with MMF and basiliximab), was associated with significant improvement in renal function at 6 months, compared to the prolonged-release tacrolimusbased regimen administered at a higher initial dose immediately after transplantation. 178 A recent nonrandomized study showed that conversion from immediate-release to prolongedrelease tacrolimus >1 month postliver transplantation limits the increase in serum creatinine concentrations. 114 It is generally accepted that methods based on serum creatinine for the detection of kidney dysfunction underestimate the extent of renal impairment in transplant recipients.…”
Section: Renal Impairmentmentioning
confidence: 99%